Soil-Agroecological Types of Lands of the Petrovsky District in the Tambov Region of Russia - Murman , Anna (KnE Life Sciences, 2021)
This article describes methodological approaches and results for digital mapping of water-migrational and erosional-accumulative soil cover structures for the forest-steppe of Tambov Plain. Such maps form the basis for applied maps such as for agroecological studies, forestry, landscape planning, etc. In this study, soil-landscape relationships were simulated as one of the subsystems of structure-functional organization. Linear discriminant analysis, random forest and the supported vector machine were used as simulation methods. The training sample consisted of 256 soil points. The Digital Elevation Model (DEM) had a spatial resolution of 25×25 meters. The simulation was provided for interfluves and valleys separately. A number of factors that describe soil cover type formation within interfluves and valleys were determined. It was established that within interfluves, determinant covariates are linked with moisture regime, whereas factors of lateral transfer and accumulation are most significant within valleys. The hierarchical nature of structure-functional organization was determined. The comparison of the results of the three simulation methods showed that the supported vector machine had the best accuracy values. However, verification by soil maps had the best correlations with the results of the linear discriminant analysis. In addition, soil-agroecological types of lands and their detailed descriptions for the key area were proposed on the basis of the simulation results of the soil combinations. Keywords: soil-agroecological types, soil cover structures, landscape-adaptive agriculture, digital soil mapping